MODEL FOR COMPLETING PATIENT RIGHTS TO RISKS INVOLVED IN HEALTH CLINIC BUSINESS - Syafruddin, Syafruddin (UNISSULA, 2022)
Fulfilment of Health is one of the main rights of every citizen. The need for the health sector, making this field one of the profitable businesses in Indonesia, one of which is a health clinic. This study explores and finds a model for fulfilling the patient's right to risk due to the beauty click business. This research is critical, provides legal certainty to patients due to the risks posed by the health clinic business. This research included the concept of doctrinal law research, which emphasizes the legal substance by analyzing legal instruments and related policies. The study results show that the patient is a customer who gets civil and criminal protection based on Article 58 paragraph (1) of Law No. 36/2009 and Article 19 paragraph (2) of Law No. 8/1999. The government or ministry of health should actively evaluate the implementation of a health clinic business to minimize medical risks caused. It means that it looks at the existence of a business license and evaluates it periodically and emphasized in the Minister of Health No. 9/2014. Nevertheless, periodic evaluation and confirmed in the Minister of Health No. 9/2014. However, periodic evaluation and confirmed in the Minister of Health No. 9/2014.